ANALISIS KOMPARASI PENILAIAN KONSUMEN TENTANG KUALITAS PELAYANAN BANK NTB SYARIAH, BRI SYARIAH DAN BANK SYARIAH MANDIRI - Fahrurrozi, Muh. (Universitas Hamzanwadi, 2019)
The research was aimed at knowing the comparison consumer assessment on NTB Syariah Bank services, BRI Syariah Bank, and Sayariah Mandiri Bank. The research method used in this research was questionnaire, while data analysis used in this research was One Way Analysis of Variance. The totality of the research result shown that Fhitung = 1.352, < Ftabel = 3.026. The totality result of variance analysis shown that there was any significant difference of consumer assessement between the quality survices among the three Syariah Banks (NTB Syariah, BRI Syariah, and Syariah Mandiri). In other words, there was a significant difference of quality services among of those three syariah Banks. Based on the amount of the mean score showed that NTB Syariah Bank = 3.59, BRI Syariah = 3.32, and Syariah Mandiri Bank = 3.27. It meant that totallity of the consumers based disposed to choose NTB syariah Bank based on the quality considaration. Based on the above testing analysis, that there was a significant difference of consumers assessement which choose NTB Syariah Bank compared with BRI Syariah and Syariah Mandiri.